2014
DOI: 10.1177/1352458514557986
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon beta-1a in multiple sclerosis: 2-year results from ADVANCE

Abstract: Objective:To evaluate the efficacy and safety of subcutaneous peginterferon beta-1a over 2 years in patients with relapsing–remitting multiple sclerosis in the ADVANCE study.Methods:Patients were randomized to placebo or 125 µg peginterferon beta-1a every 2 or 4 weeks. For Year 2 (Y2), patients originally randomized to placebo were re-randomized to peginterferon beta-1a every 2 weeks or every 4 weeks. Patients randomized to peginterferon beta-1a in Year 1 (Y1) remained on the same dosing regimen in Y2.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
163
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(186 citation statements)
references
References 18 publications
11
163
0
12
Order By: Relevance
“…37 Those statements that could not be approved during the face-to-face meeting due to time limitations were evaluated in a third round via e-mail. Extension studies available for four of the interferon pivotal trials concluded that the early-intervention group had a lower annualized relapse rate and fewer new or newly enlarging T2 lesions at 2 and 4 years' follow-up, 54,55 as well as a lower proportion of participants with disability worsening at 2 and 8 years' follow-up. 55,56 At 16 years' follow-up, there was little difference between the early-and delayed-treatment groups in the number of participants reaching an EDSS score of 6 and those converting to secondary-progressive MS. 57 Further details about the study outcomes can be found in Supplementary Appendix 8.…”
Section: Methods For Reaching Consensusmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Those statements that could not be approved during the face-to-face meeting due to time limitations were evaluated in a third round via e-mail. Extension studies available for four of the interferon pivotal trials concluded that the early-intervention group had a lower annualized relapse rate and fewer new or newly enlarging T2 lesions at 2 and 4 years' follow-up, 54,55 as well as a lower proportion of participants with disability worsening at 2 and 8 years' follow-up. 55,56 At 16 years' follow-up, there was little difference between the early-and delayed-treatment groups in the number of participants reaching an EDSS score of 6 and those converting to secondary-progressive MS. 57 Further details about the study outcomes can be found in Supplementary Appendix 8.…”
Section: Methods For Reaching Consensusmentioning
confidence: 99%
“…55,56 At 16 years' follow-up, there was little difference between the early-and delayed-treatment groups in the number of participants reaching an EDSS score of 6 and those converting to secondary-progressive MS. 57 Further details about the study outcomes can be found in Supplementary Appendix 8.…”
Section: Review Questionmentioning
confidence: 99%
“…The peginterferon beta-1a safety profile was similar to established interferon beta treatments; injection-site reactions, influenza-like symptoms, pyrexia, and headache were the most commonly reported treatment-related adverse events (AEs) [Calabresi et al 2014;Kieseier et al 2015]. Significant benefits on disability outcomes were also demonstrated: peginterferon beta-1a 125 mcg every 2 weeks reduced the risk of 12-week CDP by 38% (p = 0.038) compared with placebo in year 1 [Calabresi et al 2014], with the benefit maintained through year 2 [Kieseier et al 2015] (Supplementary Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…Its efficacy was established in the 2-year, phase III ADVANCE study, in which peginterferon beta-1a significantly reduced relapse rates and improved MRI measures, compared with placebo over 1 year, in patients with relapsing-remitting MS (RRMS), with clinical and MRI benefits maintained through year 2 [Calabresi et al 2014;Kieseier et al 2015]. The peginterferon beta-1a safety profile was similar to established interferon beta treatments; injection-site reactions, influenza-like symptoms, pyrexia, and headache were the most commonly reported treatment-related adverse events (AEs) [Calabresi et al 2014;Kieseier et al 2015].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation